KAJIAN JARINGAN IRIGASI SALURAN PRIMER PADA KAWASAN KARANG ANYER KABUPATEN SIMALUNGUN - Yusrizal Lubis; Diana Suita; Kartika Indah Sari (Jurnal Simetri Rekayasa, 2021)
The Kerasaan irrigation area is an irrigation area located in Pematang Bandar District, Simalungun Regency, North Sumatra Province. With a functional area of ​​5000 (Ha) and a primary irrigation channel area of ​​31.02 (km). In optimizing irrigation performance in the Kerasaan irrigation area, maintenance of the irrigation network infrastructure must be carried out, one of which is by evaluating the irrigation channels in the area. This evaluation aims to identify and analyze the condition and function of irrigation assets in the Kerasaan irrigation area, so as to optimize the function of the irrigation canal to irrigate the lands in the irrigation area. The method used in evaluating the irrigation canal is the observation of method by tracing the irrigation network using a tool (GPS) to find out the coordinates of the channel point and documenting asset damage with a camera/mobile phone. Based on the results of the analysis, the total length of damage to the channel structure of the pair is 10 m from a combination of several segments in 2 canals in the primary channel with a total damage index of 0.70%. In the Kerasaan primary channel from the survey results as far as (± 1500 m) in the field, there are 1 unit of side spillway building, 2 units for tapping, and 2 units of mud bag building. The results of the analysis can be used for planning the construction of irrigation buildings by planning structures, sluice gates and measuring buildings.